2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332705
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive hydrogel with embedded magnetic nanoparticles for the implementation of shrinkable medical microrobots and for targeting and drug delivery applications

Abstract: The paper describes the choice of a thermoresponsive material for the implementation of untethered medical microrobots and other microdevices. These entities can be propelled at a specific location in the body using a Magnetic Resonance Imaging (MRI) system while being actuated for various functions such as the release of drugs by a volume change induced by hyperthermia of nanoparticles embedded in the hydrogel. This paper presents some preliminary results showing that poly(N-isopropylacrylamide) (PNIPA) might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…where J m ∈ R n×n is the manipulator Jacobian. Mahoney and Abbott have shown that the velocity level kinematics (10) can also be modified to include the contri- bution of the magnetic moment of the actuator magnet using Ṁ = Ω × M, and we obtain [19] ẋ Ṁ = I 0 0 SK(M) J m (q) q = J A (q) q,…”
Section: B Rotating Actuating Magnetic Fieldsmentioning
confidence: 98%
See 1 more Smart Citation
“…where J m ∈ R n×n is the manipulator Jacobian. Mahoney and Abbott have shown that the velocity level kinematics (10) can also be modified to include the contri- bution of the magnetic moment of the actuator magnet using Ṁ = Ω × M, and we obtain [19] ẋ Ṁ = I 0 0 SK(M) J m (q) q = J A (q) q,…”
Section: B Rotating Actuating Magnetic Fieldsmentioning
confidence: 98%
“…The locomotion of these tetherless devices capitalizes on the conversion of several forms of energies into mechanical energy or movement. Magnetic [5], [6], acoustic [7], chemical [8], electric [9], thermal [10], and light [11] energy have been utilized to actuate structures fabricated specifically to work upon sensing one, or a combination [12], of these external stimuli. Once the relation between the external energy and the behavior of the stimuli-responsive material in the fabricated structures is understood, a locomotion strategy is designed to work based on the environment and the potential application.…”
Section: Introductionmentioning
confidence: 99%
“…These agents are often designed with a specific surgical tasks in mind and fabricated using sophisticated techniques [2]. Prominent examples involve: soft grippers for single-cell biopsy [3], scaffold-type robots for stem cell manipulation [4], thermoactive polymers for targeted drug delivery [5], stress-engineered MEMS microrobots [6], tubular micromotors, such as spermbots or microjets [7], and helical microswimmers [8]. With recent advancements in soft materials and microfabrication techniques, the surge of new micro-agents is expected to continue [9].…”
mentioning
confidence: 99%
“…These agents are often designed with a specic surgical tasks in mind and fabricated using sophisticated techniques [104]. Prominent examples involve: soft grippers for single-cell biopsy [227], scaold-type robots for stem cell manipulation [228], thermoactive polymers for targeted drug delivery [229], stress-engineered MEMS microrobots [230], tubular micromotors, such as spermbots or microjets [231], and helical microswimmers [232]. With recent advancements in soft materials and microfabrication techniques, the surge of new micro-agents is expected to continue [233].…”
Section: Introductionmentioning
confidence: 99%